(untitled) (Swiss Medical Weekly, 2011)
Primary mediastinal lymph node staging is important to select properly patients who can benefit from an induction treatment. The accuracy of CT scan in the evaluation of mediastinal lymph nodes is low. Further staging can be omitted in patients with negative mediastinal PET in most of the cases. PET positive findings should always be histologically or cytologically confirmed. Endoscopic techniques are accurate minimally invasive techniques mostly used to confirm a PET-positive finding but not for complete mediastinal staging. Mediastinoscopy is an invasive technique which provides a complete statging of the upper mediastinum. At least one ipsilateral, one contralateral and the subcarinal nodes should be routinely biopsied. Restaging of the mediastinum after induction treatment is necessary to select the patients who can benefit from surgery. There are no imaging techniques which can accurately determine the biological response of the tumour to the induction treatment. Neither CT, PET or PET-CT seem good enough to make further therapeutic decisions, based on their results. The accuracy of PET in mediastinal restaging is not optimal, mainly due to its low sensitivity. Fusion images with PET-CT seem to improve the results with a very favourable sensitivity, specificity and accuracy. An invasive technique providing cytohistological information is necessary. For restaging techniques, endoscopic techniques or surgical invasive techniques can be used. If they yield a positive result, definitive nonsurgical treatment seems to be indicated in most patients. Remediastinoscopy has proven to be feasible but due to adhesions and fibrosis, the intervention is technically challenging. The technique of lymph-node assessment during surgery for non-small-cell lung cancer (NSCLC) is not standardised to date. Accurate intra-operative staging is necessary to compare the results from different institutions and to conduct multi-institutional trials. Systematic mediastinal lymph-node dissection is recommended in all cases for complete resection of NSCLC and improves pathologic staging and the prospect for adjuvant therapy. The role of mediastinal lymphadenectomy regarding overall survival and local control remains controversial but systematic lymph-node dissection might be associated with a better outcome in stage I NSCLC. Lobe-specific systematic nodal dissection is acceptable for peripheral squamous T1 tumours, if hilar and interlobar nodes are negative on frozen section studies.